Association between specific social activities and depressive symptoms among older adults: A study of urban-rural differences in China - Han, Tanqian; Han, Mei; Moreira, Paulo; Song, Hongxia; Li, Ping; Zhang, Zhenlong (Frontiers in Public Health, 2023)
Background: Participation in social activities can help alleviate depressive symptoms in older adults. However, few studies have investigated the relationship between social activities and depressive symptoms in Chinese older adults. The purpose of this study was to investigate the relationship between specific social activity participation and depressive symptoms in Chinese older adults, with attention to urban-rural differences. Methods: A cross-sectional study based on data from the 2018 China Health and Retirement Longitudinal Study (CHARLS), selected from older adults aged 60 years and older. Generalized linear models were constructed to assess the effects of participants' characteristics and specific social activities on CES-D scores. Multivariate logistic regression analysis was used to explore the association between specific social activities and depressive symptoms. Results: Among the participants in this study, the prevalence of depressive symptoms was found to be 36.2% in older adults and was higher in rural older adults (39.7%) than in urban older adults (30.9%). Our results showed that for urban respondents, providing help to others (not regularly. OR=0.753, 95% CI: 0.579-0.980, P= 0.035), going to a sport (not regularly. OR=0.685, 95% CI: 0.508-0.924, P= 0.013), and using the Internet (not regular. OR= 0.613, 95% CI: 0.477-0.789, P<0.001; almost weekly. OR=0.196, 95% CI: 0.060-0.645, P=0.007) were all significantly and negatively associated with depressive symptoms, while for rural respondents, interacting with friends (not regularly. OR=1.205, 95% CI: 1.028-01.412, P= 0.021) and using the Internet (not regularly. OR=0.441, 95% CI: 0.278-0.698, P<0.001) were significantly and negatively associated with depressive symptoms. Conclusions: Our findings suggest that there is a cross-sectional association between specific social activity participation and depressive symptoms among Chinese older adults, and that this association differs between urban and rural older adults. This implies that participation in specific social activities may be important for alleviating depressive symptoms in older adults, providing a reference for government policy makers and advocates to better the mental health of older adults.